Novel potential biomarkers for predicting childhood caries via metagenomic analysis - Zhang, Hui; Zheng, Xiao; Huang, Yongmao; Zou, Yuanqiang; Zhang, Tao; Repo, Maria Alice; Yin, Meixiang; You, Yang; Jie, Zhuye; Xu, Wen-an (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundDental caries is a prevalent global health issue, particularly among children, with significant oral and overall health implications. The oral microbiome is considered a critical factor in caries development, with various microbial species implicated in the disease process.ObjectivesThis study aims to explore the changes and interactions of oral microbiota in childhood caries using metagenomic analysis, and identify potential biomarkers for early caries detection and treatment.MethodsSaliva samples were collected from 241 children aged 6 to 9 years, categorized into caries-free (CF), low-caries (CL), and caries-severe (CS) groups. Metagenomic sequencing was performed to analyze the oral microbiome, followed by a series of statistical and functional analyses to characterize microbial diversity and function.ResultsThe study revealed significant differences in the microbial community composition among the groups, with the CS group exhibiting higher alpha and beta diversity than that of the CF group. Numerous unclassified microorganisms, such as Campylobacter SGB19347 and Catonella SGB4501, are intimately linked to dental caries and display intricate interaction networks, suggesting the potential formation of a distinct ecological network. In functional assessment, we identified a possible link between pectin and caries, suggesting that microorganisms that produce pectinase enzymes might play a role in the advancement of severe dental caries. Additionally, we identified 16 species as the best marker for severe dental caries, achieving an impressive AUC of 0.91.ConclusionThe role of microbiota in dental caries is multifaceted, involving a complex interplay of microbial species and functions. Our findings enhance the understanding of the microbial basis of dental caries and offer potential diagnostic and therapeutic targets. The predictive capacity of the identified biomarkers warrants further investigation for early caries detection and intervention.Clinical SignificanceThe identification of novel biomarkers through metagenomic analysis enables early detection and targeted intervention for childhood caries, potentially transforming children dental care and significantly improving long-term oral health outcomes.